2021
DOI: 10.4269/ajtmh.20-0944
|View full text |Cite
|
Sign up to set email alerts
|

A Realist Synthesis of Community-Based Interventions in Vector-Borne Diseases

Abstract: Randomized control trials have provided evidence that some community-based interventions (CBIs) work in vector-borne diseases (VBDs). Conversely, there is limited evidence on how well those CBIs succeed in producing specific outcomes in different contexts. To conduct a realist synthesis for knowledge translation on this topic, we examined the extent to which realist concepts (context, mechanisms, and outcomes) and their relationships are present in the existing literature on CBIs for VBDs. Articles on CBIs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…40% ( n = 37) of the realist reviews cited use of an advisory group at some stage (as per the working definition for this study, notably other terminology was often reported) [14–17, 25–61]. 60% ( n = 56) did not mention the use of an advisory group [62–117]. Of those that did not mention an advisory group, seven reviews [62–64] did report participant involvement that did not fulfill the criteria of an advisory group, i.e., participants were used as data sources but did not advise on the review.…”
Section: Resultsmentioning
confidence: 99%
“…40% ( n = 37) of the realist reviews cited use of an advisory group at some stage (as per the working definition for this study, notably other terminology was often reported) [14–17, 25–61]. 60% ( n = 56) did not mention the use of an advisory group [62–117]. Of those that did not mention an advisory group, seven reviews [62–64] did report participant involvement that did not fulfill the criteria of an advisory group, i.e., participants were used as data sources but did not advise on the review.…”
Section: Resultsmentioning
confidence: 99%
“…aegypti, studies conducted mainly in the 2000s in several countries suggest that integrated community-based control of Ae. aegypti under different approaches reduced vector density and had an impact on dengue transmission [84][85][86][87][88]. These approaches, such as Socialisation of Evidence for Participatory Action [SEPA], have been used in mobilising communities for vector control in Nicaragua and Mexico, known as The Green Way, which is based on cluster randomised controlled trial added community engagement in dengue prevention.…”
Section: Approaches To Social Participationmentioning
confidence: 99%